Perbandingan Keamanan Vaksin mRNA COVID-19 Pada Ibu Hamil Dengan Ibu Tidak Hamil: Sebuah Review Sistematik - Ahmad Sabili Rifa'i; Clarishella Melvina Deinera; Bambang Satrio Utomo; Nadya Angelina; Budi Utomo; Khusnatul Mawaddah Arief (JURNAL ILMIAH DHDT - KEBIDANAN, 2022)
COVID-19 disease has spread all over the world. Some become acute respiratory distress syndrome or a more severe form of the disease that leads to death. Most of the vaccine effectiveness data currently available relate to mRNA vaccines. Pregnant women with COVID-19 are known to have a high risk of being admitted to the ICU. The increase with preterm births is still being observed in cases of complications caused by COVID-19. This research is a systematic review that uses articles. Research sources come from literature obtained from the online database Pubmed (n = 27), Web of Science (n = 18), Springerlink (n = 104) , and Science Direct (n = 266). Article searches were performed using the keywords ("vaccine") AND ("coronavirus" OR "COVID") AND ("pregnant" OR "pregnancy") AND ("mRNA" ). There were 542 women who were pregnant with the first vaccine, 526 women who were pregnant with the second vaccine, 1296 women who were not pregnant with the first vaccine, 305 women who were not pregnant with the second vaccine. Based on the data on pain symptoms at the injection site, the results did not show much different results. Then the symptoms of feeling tired were found to be more common in non-pregnant women. Furthermore, headache symptoms were found more in non-pregnant women. The symptoms of muscle pain are obtained more in non-pregnant women. From the study it can be concluded that there is no significant difference between the side effects that occur after the first dose of covid mRNA vaccination and the second dose of pregnant women and non-pregnant women